2012
DOI: 10.1111/chf.12007
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Interleukin 6 and C‐Reactive Protein Associated With Cognitive Impairment in Heart Failure

Abstract: There is abundant evidence on inflammatory mechanisms in heart failure (HF) that are used for prognostication of the disease; however, data are lacking regarding the association between elevated cytokines, C-reactive protein (CRP), and cognition in HF. A cross-sectional pilot study of 38 patients with HF, aged 62 years (standard deviation± 9 years), predominantly men (68%) and Cau casian (79%) were screened for cognitive function using the Montreal Cognitive Assessment (MoCA). The study aimed to examine cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 53 publications
2
48
0
1
Order By: Relevance
“…We assessed biomarkers known to be involved in cerebro- and/or cardiovascular disease, and cognitive impairment: interferon-γ (IFNγ), TNFα, sICAM-1, sVCAM-1, BDNF, IL-8, matrix metallopeptidase-9 (MMP-9), IL-6, CRP, and SAA [11, 13, 15, 19, 22]. After a 10-min rest period, whole blood was drawn into a 10-mL vacutainer tube preserved with EDTA while participants were in an upright sitting position.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed biomarkers known to be involved in cerebro- and/or cardiovascular disease, and cognitive impairment: interferon-γ (IFNγ), TNFα, sICAM-1, sVCAM-1, BDNF, IL-8, matrix metallopeptidase-9 (MMP-9), IL-6, CRP, and SAA [11, 13, 15, 19, 22]. After a 10-min rest period, whole blood was drawn into a 10-mL vacutainer tube preserved with EDTA while participants were in an upright sitting position.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, there is a relative lack of knowledge relating peripheral neuroinflammation biomarkers and cognitive function specifically in patients with HF. Although, one study found an inverse association between peripheral concentrations of both IL-6 and C-reactive protein (CRP) and cognitive function in patients with HF [19]. Determining definitive arrays of peripheral biomarker expression that can predict cognitive impairment and its progression would be beneficial for early diagnosis, and monitoring treatments.…”
mentioning
confidence: 99%
“…A small study of patients with NYHA II or III heart failure found that higher levels of IL-6 and CRP were associated with poorer performance on the MoCA [97]. There was no association with TNF-α.…”
Section: Cytokinesmentioning
confidence: 97%
“…These include obesity (Miller and Spencer, 2014), HIV infections (Correia et al, 2013;Hilsabeck et al, 2010), healthy older adults (Elderkin-Thompson et al, 2012;Noble et al, 2010;Simpson et al, 2013), chemotherapy (Cheung et al, 2013;Ganz et al, 2013;Kesler et al, 2013), heart failure (Athilingam et al, 2013), RA (Hamed et al, 2012), hepatitis C virus infection (Farag et al, 2011) and bipolar disorder (Bauer et al, 2014;Lotrich et al, 2014).…”
Section: Cognitive and Memory Difficulties And Inflammationmentioning
confidence: 99%